The well-grounded Java developer - Evans, Benjamin J.; Clark, Jason D.; Verburg, Martijn (Manning Publications, 2022)
Understanding Java from the JVM up gives you a solid foundation to grow your expertise and take on advanced techniques for performance, concurrency, containerization, and more. In The Well-Grounded Java Developer, Second Edition you will learn: The new Java module system and why you should use it Bytecode for the JVM, including operations and classloading Performance tuning the JVM Working with Java's built-in concurrency and expanded options Programming in Kotlin and Clojure on the JVM Maximizing the benefits from your build/CI tooling with Maven and Gradle Running the JVM in containers Planning for future JVM releases The Well-Grounded Java Developer, Second Edition introduces both the modern innovations and timeless fundamentals you need to know to become a Java master. Authors Ben Evans, Martijn Verburg, and Jason Clark distill their decades of experience as Java Champions, veteran developers, and key contributors to the Java ecosystem into this clear and practical guide. You'll discover how Java works under the hood and learn design secrets from Java's long history. Each concept is illustrated with hands-on examples, including a fully modularized application/library and creating your own multithreaded application. About the Technology Java is the beating heart of enterprise software engineering. Developers who really know Java can expect easy job hunting and interesting work. Written by experts with years of boots-on-the-ground experience, this book upgrades your Java skills. It dives into powerful features like modules and concurrency models and even reveals some of Java's deep secrets. About the Book With The Well-Grounded Java Developer, Second Edition you will go beyond feature descriptions and learn how Java operates at the bytecode level. Master high-value techniques for concurrency and performance optimization, along with must-know practices for build, test, and deployment. You'll even look at alternate JVM languages like Kotlin and Clojure. Digest this book and stand out from the pack. What's Inside The new Java module system Performance tuning the JVM Maximizing CI/CD with Maven and Gradle Running the JVM in containers Planning for future JVM releases About the Reader For intermediate Java developers. About the Authors Benjamin J. Evans is a senior principal engineer at Red Hat. Martijn Verburg is the principal SWE manager for Microsoft's Java Engineering Group. Both Benjamin and Martijn are Java Champions. Jason Clark is a principal engineer and architect at New Relic. Quotes Ben, Jason, and Martijn have done a fantastic job with this book. Take advantage of their collective wisdom. - From the Foreword by Heinz Kabutz, The Java Specialists' Newsletter True to its name, it introduces and reinforces concepts from language level down to the JVM bytecode. - Yogesh Shetty, ING Bank Great information...a worthy update. - Michael Wall, Wall Technology Consulting A deep dive into modern Java and JVM-based languages. - Gilberto Taccari, faire.ai A must-read for every Java developer, including seasoned ones! - Jean-François Morin, Laval University.